(untitled) (Economics and region, 2025)
The article examines the features of the economic approach in regulating food industry enterprises, taking into account the challenges of the modern market and industry specifics. It is studied that the use of fiscal incentives, tax breaks, subsidies and public-private partnerships contributes to sustainable development, increased competitiveness and faster adaptation to the global market. Particular attention is paid to the digital transformation of the industry, which requires flexible state support, especially for small and medium-sized businesses, as well as the introduction of preferential lending instruments, grants for innovation and R&D programs. The importance of integrating the economic approach into business processes and the risks of dependence on state support, which can reduce the independence of enterprises, is emphasized. A comprehensive regulatory model is proposed that combines innovation, equal access to resources and support mechanisms to increase the sustainability and competitiveness of the industry in the international market.